Penerapan Culturally Responsive Teaching (CRT) dalam Model Pembelajaran Understanding by Design (UbD) untuk Meningkatkan Pemahaman Konseptual Peserta Didik di SDN 19 Cakranegara - Sofyan, Muhamad; Fardin; Fitri (Mataram University, 2025)
Cultural diversity within the school environment requires learning approaches that can accommodate students’ varied experiences and backgrounds. Culturally Responsive Teaching (CRT) is a teaching strategy that connects learning materials to students’ cultural contexts, while Understanding by Design (UbD) emphasizes planning based on deep conceptual understanding. The integration of CRT within the UbD framework is expected to enhance students’ conceptual comprehension by providing more contextual and meaningful learning experiences. This study employed a Classroom Action Research (CAR) method conducted in four cycles consisting of planning, action, observation, and reflection. The research subjects were fourth-grade students at SDN 19 Cakranegara. Data were collected through conceptual understanding tests, classroom observations, and interviews with teachers and students. The results showed that the CRT-UbD approach progressively improved students’ conceptual understanding across all cycles. Students demonstrated greater ability to relate learning materials to real-life contexts, participated more actively in discussions, and showed increased learning motivation. Teachers also reported that the approach helped them design more adaptive and inclusive instruction. In conclusion, the application of CRT within the UbD model is effective in improving students’ conceptual understanding and can be implemented in culturally diverse school settings to create more relevant and meaningful learning experiences.